1993
DOI: 10.1161/01.cir.88.5.2307
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between aberrant ventricular conduction and ventricular ectopy in atrial fibrillation using RR interval scattergram.

Abstract: We conclude that the RR interval scattergram makes it possible to differentiate between aberrant ventricular conduction and ventricular ectopy in atrial fibrillation, and thus, it is a useful noninvasive clinical tool.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…Because of the high HR during exercise, presence of P waves often cannot be ascertained, thus differentiating wide QRS complex tachycardias as ventricular versus supraventricular in origin may be difficult or impossible. We were not able to differentiate the 2 conduction patterns in our study, because doing so would require intracardiac His bundle electrocardiography recordings . The treadmill test is considered a stressful experience for horses, leading to high sympathetic stimulation, which may explain the HR increase initiated during the warm‐up period, permitting a high number of atrial impulses to be transmitted through the AV node.…”
Section: Discussionmentioning
confidence: 97%
“…Because of the high HR during exercise, presence of P waves often cannot be ascertained, thus differentiating wide QRS complex tachycardias as ventricular versus supraventricular in origin may be difficult or impossible. We were not able to differentiate the 2 conduction patterns in our study, because doing so would require intracardiac His bundle electrocardiography recordings . The treadmill test is considered a stressful experience for horses, leading to high sympathetic stimulation, which may explain the HR increase initiated during the warm‐up period, permitting a high number of atrial impulses to be transmitted through the AV node.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison, the reported prevalence of VPDs during exercise in clinically healthy dressage and showjumping horses is 5% [25] and 18% [26]. In human patients, wide QRS complexes are frequently observed in AF [27]. Two different processes could be causing this broadening: ventricular ectopy or aberrant intraventricular conduction of supraventricular impulses [28].…”
Section: Discussionmentioning
confidence: 99%
“…al. [56] demonstrated that pairs of RR intervals constructed with aberrant conduction beats were distributed along the lower envelope of the Poincaré plot. Similarly, the coupling points of wide QRS complexes are also distributed along the envelope of the Poincaré plot [103].…”
Section: Discussionmentioning
confidence: 98%
“…the regularity of the ventricular rhythm. In a Poincaré plot, each RR interval is plotted versus the preceding one [54,55,56]; it should be noted that this type of plot is also referred to as the Lorenz plot. It allows a beat-to-beat approach of HRV detecting pattern resulting from non linear processes and it was presented as a clinically useful tool for the study of AV nodal characteristics in AF.…”
Section: Analysis Of the Ventricular Response During Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation